A Cross-sectional Study on Factors Influencing Health Services Utilisation for under-Five Morbidities in South Bengaluru - Ravish Haradanhalli; Nitu Kumari; Ramya Mandya; Jithin Surendran (Journal of Community Health Research, 2023)
Background: World Health Organization (WHO) estimates that seeking prompt and appropriate healthcare could reduce child deaths by nearly 30%.  In this background, the present study was conducted to 1. assess the health services utilization for diarrhoea and ARI (acute respiratory infections) among under-5 children in South Bengaluru, 2. determine the factors influencing mothers for utilization of health services. Methods: Authors conducted a cross-sectional study in 10 randomly selected wards of South Bengaluru from July, 2019 to January, 2020 using multistage sampling. 432 mothers with under-5 children were interviewed regarding morbidities of their children in the previous one month and the health services they utilised, using a semi-structured questionnaire derived from multiple indicator cluster survey (MICS) by UNICEF. Data were analysed using SPSS 21.0 for descriptive statistics and logistic regression. Results: 95 of the participants had illnesses in the past one month; but, only 41 had used health facilities for treatment, mainly in the private sector (68.3%). The reasons for non-utilization of healthcare services were negligence (36.9%), long waiting time at the center (22.4%), financial constraints (20.4%) and mothers’ jobs (9.6%). The most significant factors influencing the health services utilisation were: literacy status of the mother (predisposing factor), low socio-economic status/ BPL (below poverty line) families (enabling factor), and severity of symptoms (need factor). Conclusion: Utilisation of healthcare services for under-five morbidities in the studied population was inadequate. The influencing factors have to be addressed on a priority basis to fulfil the goal of universal health coverage.